Neuromuscular Blocking Agents and Monitoring in China: A Cross-Sectional Survey of Current Management - Wu, HaoTian; Lin, ZengMao; Zhou, RuiHao; Huang, SuiSui; Chen, LingJun; Su, Yang; Cheng, LuoNa; Zhang, Huan (Frontiers in Medicine, 2022)
Background Little is known about the recent use of neuromuscular blocking agents (NMBAs) and monitoring in China. This paper presents the results of a nationwide survey conducted to obtain information regarding the current management of NMBAs in China. Methods A questionnaire was sent to Chinese anesthesiologists inviting them to participate in the study. The questionnaire was available through the wenjuanxing website, and the link was sent to 1,488 anesthesiologists using the Wechat mini app. Results The web-based survey consisted of 28 questions, and data were collected using an online tool. Between May 19, 2021 and June 16, 2021, 637 responses were collected (response rate = 42.8%). Only 10.2% of anesthesiologists reported using neuromuscular function monitors, and 6.59% of respondents reported that they had the relevant monitors in the operating room. Conclusion Although PORC is a potential safety issue, the frequency of using reversal agents and monitors remains extremely low in China. Surveys such as this are important to understand the use and application customs of NMBAs in China.